Comparison of biomechanical effects of polyetheretherketone (PEEK) rods and titanium rods in lumbar long-segment instrumentation: a finite element study - Li, Chao; Zhao, Yao; Qi, Longtao; Xu, Beiyu; Yue, Lei; Zhu, Ranlyu; Li, Chunde (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Polyetheretherketone (PEEK) lumbar fusion rods have been successfully used in short-segment posterior instrumentation to prevent adjacent segment degeneration. However, limited studies have reported their application in lumbar long-segment instrumentation. This study aimed to compare the biomechanical performances of PEEK rods and titanium rods in lumbar long-segment instrumentation using finite element (FE) models, with the expectation of providing clinical guidance.: A lumbar FE model (A) and four lumbar fixation FE models (BI, CI, BII, CII) of the L1-S1 vertebral body were developed using CT image segmentation (A: intact model; BI: intact model with L2-S1 PEEK rod internal fixation; CI: intact model with L2-S1 titanium rod internal fixation; BII: intact model with L3-S1 PEEK rod internal fixation; CII: intact model with L3-S1 titanium rod internal fixation). A 150-N preload was applied to the top surface of L1, similar to the intact model. The stresses on the lumbar intervertebral disc, facet joint, pedicle screws, and rods were calculated to evaluate the biomechanical effect of the different fixation procedures in lumbar long-segment instrumented surgery.Results: Under the four physiological motion states, the average stresses on the adjacent segment intervertebral disc and facet joint in all fixation models were greater than those in the intact model. Furthermore, the average stresses on the adjacent segment intervertebral disc and facet joint were greater in models CI and CII than in models BI and BII, respectively. The average stresses on the pedicle screws and rods were decreased in models BI and BII compared with models CI and CII under the four physiological motion states, respectively.The PEEK rod internal fixation system may have better biomechanical properties than the titanium rod internal fixation system in delaying adjacent segment degeneration, improving the lumbar function of postoperative patients, and reducing the risk of screw loosening and breakage in lumbar long-segment instrumentation.